2011
DOI: 10.1007/s00167-011-1659-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the medial patello-femoral and patello-tibial ligaments for treatment of patellar instability

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 21 publications
2
51
0
8
Order By: Relevance
“…The statistical verification of our hypothesis leads to the conclusion that the MR plays an important role as a medial stabiliser of the patella, especially in low angles of flexion, since from 20 o to 90 o of knee flexion, the interaction of bones is an additional contribution to the stability of the patella, which is in concordance with the literature [6,13]. The MPFL and MPML are major stabilisers, contributing up to 50-60% and 24%, respectively, while MR and MPTL contributes up to 13% [5,13]. VMO also plays an important role, especially in the first 20-30 o of flexion, due to the meshing of its fibres to MPFL, reinforcing MPFLs stabilising role [13].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The statistical verification of our hypothesis leads to the conclusion that the MR plays an important role as a medial stabiliser of the patella, especially in low angles of flexion, since from 20 o to 90 o of knee flexion, the interaction of bones is an additional contribution to the stability of the patella, which is in concordance with the literature [6,13]. The MPFL and MPML are major stabilisers, contributing up to 50-60% and 24%, respectively, while MR and MPTL contributes up to 13% [5,13]. VMO also plays an important role, especially in the first 20-30 o of flexion, due to the meshing of its fibres to MPFL, reinforcing MPFLs stabilising role [13].…”
Section: Discussionsupporting
confidence: 88%
“…In most studies the outcomes were positive, showing that the MR plays an important role as a stabilising factor for the patella. There have also been studies comparing methods of MR repair and repair of other medial stabilisers, such as the vastus medialis [20] and MPFL [21], showing that MPFL is a better static stabiliser compared to MR. Studies dealing with MPFL repair alone also showed good clinical results, reinforcing the view that MPFL is the main stabiliser against lateral displacement of the patella [4,5,10,11,12,17,19], especially in lower angles of flexion.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[13][14][15][16][17] The only difference in our proposed procedure involves the grafts used. The use of the quadricipital and patellar grafts for the reconstruction of the MPFL is already well-known and widespread, and the use of the patellar tendon for isolated reconstruction of the MPTL has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports in the literature have described case series of combined MPFL and MPTL reconstructions, mostly in children, with good results. [13][14][15][16][17] These reconstructions use the semitendinosus or gracilis tendons with preservation of their tibial insertions, which does not coincide with the anatomic insertion of the MPTL. Reconstruction of the MPTL with the patellar tendon associated with procedures other than MPFL reconstruction (lateral retinacular lengthening, vastus medialis obliquus advancement, medial retinaculum closure, and tibial tuberosity osteotomy) has also been described with good outcomes.…”
mentioning
confidence: 99%